KAJIAN KUALITAS LINGKUNGAN KERJA DAN PENERAPAN STANDAR OPERASIONAL PROSEDUR BENGKEL SERVIS KENDARAAN TERHADAP KESEHATAN PEKERJA MEKANIK SEPEDA MOTOR DI KOTA DENPASAR - Juli Arsana, I M.; Redi Aryanta, I W.; Sudana, I. B. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 9 No 2 (2015), 2015)
Increasing the number and motorcycle ownership provides increased workload and environmental load in the vehicle workshop. This research was conducted with the aim of analyzing the influence of the quality of the working environment and the application of standard operating procedures work vehicle servicing workshop on the health of workers mechanical workshop in Denpasar. Environmental variables measured in the form of CO (carbon monoxide), dust, lighting, noise and work climate as well as assessing the implementation of labor standard operating procedures vehicle repair workshop. Also assessed lung function, musculoskeletal complaints and fatigue were identified employee. Analysis of data using simple regression to the effect of each variable was continued regression to assess the influence of several variables on the health of the mechanical environment. Significance value used is á = 0.15 (CI = 85%). From 20 workshops and 101 workers were examined as a mechanic samples were obtained the following results: the working environment workshop dust parameter exceeds the quality standards. For the implementation of standard operating procedures parameters in a motorcycle shop can not all be met. Motorcycle mechanic workers were found to have complaints on lung function, musculoskeletal and experience fatigue. From the analysis it was found that all the variables on the quality of the environment and the implementation of standard work procedures workshop has a relationship to the health of workers motorcycle mechanic in Denpasar, but the only variable ambient CO (R> 0.697) and dust working environment (R = 0.612) were influential significantly (R> 0.50).
Keywords: Work Environment; Motorcycle Workshop; Health; Mechanical Workers